1993
DOI: 10.1007/bf03258446
|View full text |Cite
|
Sign up to set email alerts
|

Single Dose and Steady-State Pharmacokinetic Profiles of Nifedipine GITS Tablets in Healthy Elderly and Young Volunteers

Abstract: The pharmacokinetics of a once-daily extended-release nifedipine formulation [Gastro-Intestinal Therapeutic System (GITS)] was studied in 23 young males and 24 elderly male and female volunteers, after single and multiple dosing of 60mg nifedipine GITS tablets once daily for 7 days, in an open nonrandomised study. Serial blood samples for plasma nifedipine levels were drawn on days I and 7, and the pharmacokinetic profiles of the elderly and young volunteers were compared after both single and multiple dosing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Interval between last nifedipine GITS and delivery (hours) log U (micrograms/l) Previous studies with nifedipine GITS in nonpregnant healthy volunteers have shown wide interindividual variability of plasma drug concentrations. [6][7][8] Our own preliminary data under nonstandardised conditions confirmed this finding in pregnant women (n = 44, doses ranging from 30 through 170 mg/day, giving concentrations ranging from 2.1 through 208 micrograms/l). 10 The nonstandardised handling of the blood samples possibly accounting in this recent pilot study for such variability included coadministration with food, timing not from nifedipine steady state (ideally between 12 and 24 hours after the last dose), exposure of the samples to light before or after centrifugation, and no immediate centrifugation of the samples).…”
Section: Commentsupporting
confidence: 70%
See 2 more Smart Citations
“…Interval between last nifedipine GITS and delivery (hours) log U (micrograms/l) Previous studies with nifedipine GITS in nonpregnant healthy volunteers have shown wide interindividual variability of plasma drug concentrations. [6][7][8] Our own preliminary data under nonstandardised conditions confirmed this finding in pregnant women (n = 44, doses ranging from 30 through 170 mg/day, giving concentrations ranging from 2.1 through 208 micrograms/l). 10 The nonstandardised handling of the blood samples possibly accounting in this recent pilot study for such variability included coadministration with food, timing not from nifedipine steady state (ideally between 12 and 24 hours after the last dose), exposure of the samples to light before or after centrifugation, and no immediate centrifugation of the samples).…”
Section: Commentsupporting
confidence: 70%
“…[6][7][8] In cardiovascular patients, therapeutic blood levels are 10-100 micrograms/l. 9 We observed wide variability in nifedipine concentrations above this range in women undergoing tocolysis with nifedipine GITS tablets £150 mg/day.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in therapeutic doses, the time to peak plasma concentration is known to be highly variable, as late as 24 hours, and may be affected by other stomach contents. 5,6 In supratherapeutic ingestions, high levels of the drug may persist for several days.…”
Section: Pharmacokinetics and Toxic Effectsmentioning
confidence: 99%
“…Apparent nifedipine C max values (normalised to a 60mg daily dose) after With respect to age, no or only slight differences were found in nifedipine GITS pharmacokinetic parameters after single or multiple doses in young and elderly volunteers, and thus no dosage adjustment is apparently necessary. [26,43] Similarly, impaired renal function in patients does not appear to significantly affect the plasma concentrations of nifedipine even following multiple doses of the nifedipine GITS, and thus dosage adjustment seems unnecessary. [27] Food does not alter the bioavailability of this device ; however, an increase in the drug absorption rate with food has been reported.F'l Some fluctuations in plasma nifedipine concentrations are apparent during multiple dosage with the GITS, due perhaps, in part, to carry-over from the dose of the previous day.…”
Section: 2 Nifedipine Gits Pharmacokineticsmentioning
confidence: 99%